2007
DOI: 10.1016/j.dam.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

On the edge-connectivity and restricted edge-connectivity of a product of graphs

Abstract: The product graph G m * G p of two given graphs G m and G p was defined by Bermond et al. [Large graphs with given degree and diameter II, J. Combin. Theory Ser. B 36 (1984) 32-48]. For this kind of graphs we provide bounds for two connectivity parameters ( and , edge-connectivity and restricted edge-connectivity, respectively), and state sufficient conditions to guarantee optimal values of these parameters. Moreover, we compare our results with other previous related ones for permutation graphs and cartesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It has been shown that λ p ( G ) ≤ ξ p ( G ) for many graphs [4,6,16,21,28,30] and sufficient conditions to establish that λ p (G ) = ξ p (G ) have been given in [4,18,26] among others.…”
Section: Article In Pressmentioning
confidence: 99%
“…It has been shown that λ p ( G ) ≤ ξ p ( G ) for many graphs [4,6,16,21,28,30] and sufficient conditions to establish that λ p (G ) = ξ p (G ) have been given in [4,18,26] among others.…”
Section: Article In Pressmentioning
confidence: 99%
“…The connectivity of graph products was also studied in [1] and [2] where the authors determine connectivity properties of the * -product, and use these properties to construct networks with high fault-tolerance. The * -product was first defined in [3] and is a concept which is more general than the Cartesian product of graphs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fàbrega and Fiol [9,10] generalized the concept of connectivity and edge-connectivity proposed by Harary [11], to k-extra connectivity and k-extra edge-connectivity. [1,5,6,13,17,18,20,21,27,34]. Hsieh and Chang [17] discussed the 3-extra connectivity of a k-ary n-cube for k ≥ 4 and n ≥ 5.…”
Section: Introductionmentioning
confidence: 99%